Role of PDE2A in cAMP/PKA signaling compartmentalization - de Oliveira Jones Ferrão Lobo, M (2018)
Background and Aims : cAMP/PKA signaling is compartmentalized within the cell, with tight spatial and temporal control of signal propagation underpinning specificity of response. The cAMP-degrading enzymes, phosphodiesterases (PDEs), are key regulators of this process. They are situated in specific subcellular domains within which they control local cAMP levels. Several components of the cAMP/PKA cascade have been identified in different mitochondrial compartments, including isoform 2 of PDE2A and multiple A-kinase anchoring proteins, suggesting the presence of multiple cAMP/PKA signaling domains within the organelle. The aims of this project were to examine the role of PDE2A in cAMP/PKA signaling compartmentalization and its biological function, with a particular focus on its role at the mitochondria. Methods : Real-time PCR and fluorescence imaging were used to assess PDE2A expression and localization in different cell lines and tissues. Co-immunoprecipitation (Co-IP) was used to validate PDE2A2 interactors. Co-IP, electron microscopy and live-cell imaging were used to explore the role of PDE2A2 at the mitochondria. Fluorescence Resonance Energy Transfer (FRET) was used to investigate the involvement of PDE2A on endoplasmic reticulum (ER) Ca2+ handling and local cAMP/PKA dynamics. Results : PDE2A2 localizes to the outer mitochondria membrane and intermembrane space and it interacts with several mitochondria and ER proteins, including components of the MINOS (mitochondrial inner membrane organizing system) complex and Caveolins. Functionally, PDE2A2 is involved in mitochondria degradation by mitophagy while PDE2A1 seems to be involved in the regulation of Ca2+ release from the ER. Phosphatases are responsible for the differential PKA dynamics between cytosol and ER. Conclusions : PDE2A isoforms localize to different compartments and are involved in distinct cellular functions. The data presented in this thesis demonstrate that PDE2A2 activity at the mitochondria controls mitochondria clearance by mitophagy. This mechanism is dysregulated in multiple pathological conditions, making PDE2A2 a potential therapeutic target.